Making Wine for the People’s Taste: The Emergence of the Argentine Wine Industry, 1885–1915 - Stein, Steve (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
It is common to use the adjective infant when referring to the early development of any industry. For the Argentine wine industry, adulthood came shockingly fast. Take-off began in 1885 with completion of the rail connection between the province of Mendoza, the major production area, and Buenos Aires, the primary consumer market. Between 1901 and 1915 alone, production rose 90.4 percent, permitting what had been an artisan industry to become the fifth-largest wine producer in the world. The major component for the emergence of the wine industry was the enormous wave of largely Mediterranean immigrants who arrived in the country. This article explores the various factors that explain Argentina’s explosive wine industry growth. They include entrepreneurial decision-making, the importation and adaptation of technology, the role of a supportive national state, and most importantly, the impact that immigrant consumers’ wine culture and expectations had on the formation of what would subsequently be a century-long model of winemaking in Argentina.